A small multigene family encodes Gi signal-transduction proteins. - Beals, C R (1987)
The guanine nucleotide-binding regulatory proteins known as G proteins are receptor-associated signal-transduction molecules that are implicated in the control of a variety of metabolic processes. Recent evidence suggests that G proteins may mediate B-lymphocyte responses to bacterial lipopolysaccharide and may also transduce signals from the T-cell antigen receptor. Since these receptors are uniquely expressed on lymphoid cells, we used molecular cloning strategies to ask whether lymphocytes contain specialized G-protein alpha subunits to assist in signal transduction. Comparison of our two deduced human alpha i amino acid sequences with those previously determined for bovine and rodent G proteins permits the identification of three closely related but distinct types of alpha i molecules that comprise a small multigene family. Using gene-specific probes, we found that both of our alpha i genes are expressed in most cell types but in differing ratios. Our data support the view that a modest repertoire of extremely closely related G proteins mediates the transduction of signals derived from multiple different receptor molecules.